Localized osmotic stress activates systemic responses to N limitation in Medicago truncatula–Sinorhizobium symbiotic plants - Martin, Marie-Laure; Pervent, Marjorie; Lambert, Ilana; Colella, Stefano; Tancelin, Mathilde; Severac, Dany; Clément, Gilles; Tillard, Pascal; Frugier, Florian; Lepetit, Marc (Frontiers in Plant Science, 2023)
In mature symbiotic root nodules, differentiated rhizobia fix atmospheric dinitrogen and provide ammonium to fulfill the plant nitrogen (N) demand. The plant enables this process by providing photosynthates to the nodules. The symbiosis is adjusted to the whole plant N demand thanks to systemic N signaling controlling nodule development. Symbiotic plants under N deficit stimulate nodule expansion and activate nodule senescence under N satiety. Besides, nodules are highly sensitive to drought. Here, we used split-root systems to characterize the systemic responses of symbiotic plants to a localized osmotic stress. We showed that polyéthylène glycol (PEG) application rapidly inhibited the symbiotic dinitrogen fixation activity of nodules locally exposed to the treatment, resulting to the N limitation of the plant supplied exclusively by symbiotic dinitrogen fixation. The localized PEG treatment triggered systemic signaling stimulating nodule development in the distant untreated roots. This response was associated with an enhancement of the sucrose allocation. Our analyses showed that transcriptomic reprogramming associated with PEG and N deficit systemic signaling(s) shared many targets transcripts. Altogether, our study suggests that systemic N signaling is a component of the adaptation of the symbiotic plant to the local variations of its edaphic environment.